Cardiotoxicity and pro-inflammatory effects of the immune checkpoint inhibitor Pembrolizumab associated to Trastuzumab. (1st October 2019) - Quagliariello, V.; Passariello, M.; Coppola, C.; Rea, D.; Barbieri, A.; Scherillo, M.; Monti, M.G.; Iaffaioli, R.V.; De Laurentiis, M.; Ascierto, P.A.; Botti, G.; De Lorenzo, C.; et al.
Abstract: Background: The immunotherapy has revolutionized the world of oncology in the last decades with considerable advantages in terms of overall survival in cancer patients. The association of Pembrolizumab and Trastuzumab was recently proposed in clinical trials for the treatment of Trastuzumab-resistant advanced HER2-positive breast cancer. Although immunotherapies are frequently associated with a wide spectrum of immune-related adverse events, the cardiac toxicity has not been properly studied. Purpose: We studied, for the first time, the putative cardiotoxic and pro-inflammatory effects of Pembrolizumab associated to Trastuzumab. Methods: Cell viability, intracellular calcium quantification and pro-inflammatory studies (analyses of the production of Interleukin 1β, 6 and 8, the expression of NF-kB and Leukotriene B4) were performed in human fetal cardiomyocytes. Preclinical studies were also performed in C57BL6 mice by analyzing fibrosis and inflammation in heart tissues. Results: The combination of Pembrolizumab and Trastuzumab leads to an increase of the intracellular calcium overload (of 3 times compared to untreated cells) and to a reduction of the cardiomyocytes viability (of 65 and 20–25%, compared to untreated and Pembrolizumab or Trastuzumab treated cells, respectively) indicating cardiotoxic effects. Notably, combination therapy increases the inflammation of cardiomyocytes by enhancing the expression of NF-kB and Interleukins. Moreover, in preclinical models, the association of Pembrolizumab and Trastuzumab increases the Interleukins expression of 40–50% compared to the single treatments; the expression of NF-kB and Leukotriene B4 was also increased. Conclusion: Pembrolizumab associated to Trastuzumab leads to strong cardiac pro-inflammatory effects mediated by overexpression of NF-kB and Leukotriene B4 related pathways. Highlights: Pembrolizumab associated to Trastuzumab has cardiotoxic effects in human fetal cardiomyocytes. Pembrolizumab and Trastuzumab increase the intracellular calcium overload in cardiomyocytes. Mice treated with Pembrolizumab and Trastuzumab have increased cardiac levels of Leukotrienes B4. Pembrolizumab associated to Trastuzumab increases the cardiac production of Interleukin-1β.